2020
DOI: 10.1158/1535-7163.mct-19-0536
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Available Tubulin Inhibitor, VERU-111, Suppresses Triple-Negative Breast Cancer Tumor Growth and Metastasis and Bypasses Taxane Resistance

Abstract: Triple-negative breast cancer (TNBC) accounts for approximately 15% of breast cancer cases in the United States. TNBC has poorer overall prognosis relative to other molecular subtypes due to rapid onset of drug resistance to conventional chemotherapies and increased risk of visceral metastases. Taxanes like paclitaxel are standard chemotherapies that stabilize microtubules, but their clinical efficacy is often limited by drug resistance and neurotoxicities. We evaluated the preclinical efficacy of a novel, pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 57 publications
(77 reference statements)
0
49
2
Order By: Relevance
“…A375 cells are one of the most widely used and representative V600E mutant melanoma cells, and we have previously reported the anti-tumor efficiency of VERU-111 in many cancer types ( Kashyap et al, 2019 ; Deng et al, 2020 ; Kashyap et al, 2020 ; Mahmud et al, 2020 ) as well as the synergy of Vem in combination with ABI-274 in A375 Vem-resistant melanoma cells ( Wang et al, 2014 ). Herein, we investigate whether the combination of VERU-111 (ABI-274 derivative) with Vem can also overcome Vem-resistance in A375.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A375 cells are one of the most widely used and representative V600E mutant melanoma cells, and we have previously reported the anti-tumor efficiency of VERU-111 in many cancer types ( Kashyap et al, 2019 ; Deng et al, 2020 ; Kashyap et al, 2020 ; Mahmud et al, 2020 ) as well as the synergy of Vem in combination with ABI-274 in A375 Vem-resistant melanoma cells ( Wang et al, 2014 ). Herein, we investigate whether the combination of VERU-111 (ABI-274 derivative) with Vem can also overcome Vem-resistance in A375.…”
Section: Resultsmentioning
confidence: 99%
“…Although combinations of BRAF inhibitor with MEK or ERK inhibitors benefit Vem-resistant patients ( Atefi et al, 2011 ; Gadiot et al, 2013 ; Pulkkinen et al, 2020 ), half of the patients still gain resistance after 6–8 months. Intriguingly, some tubulin destabilizing agents reported previously by us targeting the colchicine-binding site showed promise to overcome Vem-resistance, paclitaxel-resistance in melanoma, breast cancer, lung cancer, prostate cancer, cervical cancer et al ( Wang et al, 2014 ; Guan et al, 2017 ; Arnst et al, 2018 ; Deng et al, 2020 ; Kashyap et al, 2020 ; Mahmud et al, 2020 ). In our previous studies, we have demonstrated that a tool tubulin inhibitor, ABI-274, showed strong synergistic efficacy in a Vem-resistant xenograft mouse model ( Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Tax plays a significant role in the treatment of breast cancer at both early and advanced stages [ 4 ]. As standard chemotherapies to stabilize microtubules, the clinical effects of Tax are frequently restricted by drug resistance and neurotoxicity [ 5 ]. Adriamycin (Adr) is another important and frequently applied chemotherapy agent in the treatment of breast cancer, with 2 key mechanisms: DNA damage and generation of reactive oxygen species [ 6 ].…”
Section: Introductionmentioning
confidence: 99%